Antithrombotic monotherapy for stable coronary artery disease and atrial fibrillation patients with and without prior coronary artery revascularization: Insights from the AFIRE trial. (25th January 2023) - Noda, T; Nochioka, K; Kaikita, K; Akao, M; Ako, J; Matoba, T; Nakamura, M; Miyauchi, K; Hagiwara, N; Kimura, K; Hirayama, A; Matsui, K; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Japan Cardiovascular Research Foundation under a contract with Bayer Yakuhin Background: The AFIRE (Atrial Fibrillation and Ischemic Events With Rivaroxaban in Patients With Stable Coronary Artery Disease) trial demonstrated that rivaroxaban monotherapy was noninferior to combination therapy with rivaroxaban plus a single antiplatelet therapy regarding efﬁcacy and superior for safety endpoints in patients with atrial fibrillation and stable coronary artery disease including patients not requiring revascularization [prior percutaneous coronary intervention (PCI) or bypass grafting (CABG)]. Purpose: The aim of this post-hoc subgroup analysis was to investigate the efficacy and safety of rivaroxaban monotherapy compared to combination therapy in patients with and without prior revascularization. Methods: Among 2, 215 patients included in the modified intention-to-treat analysis in the AFIRE trial, 1445 patients (65.2%) had undergone previous PCI alone, and 252 (11.4%) had undergone previous CABG. The remaining 518 patients (23.4%) was categorized as a group without prior revascularization and then compared with a group with prior revascularization (PCI or CABG). The primary efficacy end point was a composite of stroke, systemic embolism, myocardial infarction, unstable angina requiring revascularization, or death from any cause. The primary safety end point was major bleeding, according to the criteria of the International Society on Thrombosis and Hemostasis. Results: In 1697 patients with prior revascularization, efficacy and safety endpoints of rivaroxaban monotherapy were superior to combination therapy (efficacy: HR 0.62, 95%CI 0.45-0.85, p=0.003; safety: HR 0.62, 95%CI 0.39-0.98, p=0.040), whereas there were no significant differences in efficacy and safety endpoints among 518 patients without prior revascularization (efficacy: HR 1.19, 95%CI 0.67-2.11, p=0.553; safety: HR 0.47, 95%CI 0.18-1.26, p=0.125). There was a borderline interaction of efficacy endpoint (P for interaction=0.055) by randomized treatment assignment (Figure 1 and Figure 2). Compared with combination therapy, the safety benefit of rivaroxaban monotherapy on any bleeding was significant in patients without prior revascularization (HR 0.59, 95%CI 0.38-0.93, p=0.022). Conclusions: In patients with prior PCI or CABG, rivaroxaban monotherapy resulted in more favorable safety and efficacy outcomes than combination therapy. There was a borderline interaction for primary efficacy outcome between prior revascularization and anti-thrombotic therapy. Figure 1 Figure 2